2022
DOI: 10.24867/ijiem-2022-1-299
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0 enabling technologies for increasing operational flexibility in final assembly

Abstract: The manufacturing industry is facing uncertainties caused by growing competition and increasing customer demands. Simultaneously, the fourth industrial revolution, commonly referred to as Industry 4.0, is helping in modernising the manufacturing industry. In the process of modernising, companies are now capable of building resilience into their systems. This resilience is in the form of higher operational flexibility, which helps cope with the growing uncertainties. The new technologies under the Industry 4.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Several definitions for softbots are influenced by the application domain they were applied to [27]. As an attempt to provide a generalized view of softbots from the system requirements point of view, some selected works have been analysed [14,27,40,[59][60][61][62][63][64][65][66][67][68][69], and the following properties for a "near-complete" softbot could be identified: • (Some level of) Security to protect itself from external malicious attacks and from being accessed by non-authorized actors. • (Some level of) Self-management to evaluate itself against its goals and performance metrics; supervise the execution of its actions; monitor the computing environment it is running in and its execution status; and be resilient to take proper measures to remain alive.…”
Section: Softbots Propertiesmentioning
confidence: 99%
“…Several definitions for softbots are influenced by the application domain they were applied to [27]. As an attempt to provide a generalized view of softbots from the system requirements point of view, some selected works have been analysed [14,27,40,[59][60][61][62][63][64][65][66][67][68][69], and the following properties for a "near-complete" softbot could be identified: • (Some level of) Security to protect itself from external malicious attacks and from being accessed by non-authorized actors. • (Some level of) Self-management to evaluate itself against its goals and performance metrics; supervise the execution of its actions; monitor the computing environment it is running in and its execution status; and be resilient to take proper measures to remain alive.…”
Section: Softbots Propertiesmentioning
confidence: 99%
“…Cobots are industrial robots designed to work alongside a human operator; the ISO/TS 15066:2016 technical specification emphasises external safety features required when using a collaborative robot [9]. Collaborative Robot Applications (CRAs) thus encompass additional safety features necessary for a safer collaboration with a human operator [10]. In major surveys conducted by Vicentini [4], Liu et al [11], and Matheson [2], the development and use of collaborative robots over the last few decades, are highlighted.…”
Section: Collaborative Robots (Cobots)mentioning
confidence: 99%
“…In major surveys conducted by Vicentini [4], Liu et al [11], and Matheson [2], the development and use of collaborative robots over the last few decades, are highlighted. One of the significant factors behind this development is the need for higher flexibility in adapting to fast-changing manufacturing environments [10]. The International Federation of Robotics (IFR) figures show, on average, 6% growth in the application of cobots [12].…”
Section: Collaborative Robots (Cobots)mentioning
confidence: 99%
“…The authors found that product-related services, like repairs, maintenance, and training, were the most important nodes from a service perspective, and that from the standpoint of digital technologies, cyber security, Big Data analytics, the Internet of Things, cloud computing and digital twins are the most significant nodes. Through the use of the new technologies commonly included in Industry 4.0, the authors of [7] claim that operational flexibility can be increased. The most common definition of operational flexibility is that it is the ability of a system to respond to changing conditions [8], and is often described as a mixture of various forms of flexibility and as having different types of sources.…”
Section: Literature Review: Relevant Landscape-resource Efficiency Ma...mentioning
confidence: 99%